Death distress constructs: A preliminary empirical examination of the Farsi form in nurses: A brief note. Issue 4 (23rd March 2020) - Dadfar, Mahboubeh; Lester, David
Abstract: Aim: Death distress can increase mental health problems. The aim of the present study was to develop a measure of death distress and evaluate the reliability of this Death Distress Scale‐Farsi (DDS‐F) among nurses. The hypotheses were that death distress has three components and that the DDS‐F would have desirable psychometric properties. Design: A descriptive cross‐sectional study. Methods: A convenience sample of 106 Iranian nurses from two hospitals at Tehran city, Iran was recruited. They completed the Death Anxiety Scale (DAS), the Death Depression Scale (DDS) and the Death Obsession Scale (DOS). Results: Cronbach's α for the DDS‐F was 0.71. As expected, the DDS‐F had three independent components: death obsession, death depression and death anxiety. A principle component analysis with a varimax rotation of the DDS‐F items identified three factors accounting for 66.13% of the variance. Factor 1 was labelled "Death Obsession" (31.3% of the variance), Factor 2 was labelled "Death Depression" (21.9% of the variance), and Factor 3 was labelled "Death Anxiety" (12.8% of the variance). Discussion: Death distress has three components: death obsession, death depression and death anxiety. The DDS‐F which measures these has good psychometric properties, and it can be used in hospital settings to assess death distress among Iranian nurses.